PERLINDUNGAN HUKUM BAGI PEMBELI SATUAN RUMAH SUSUN AKIBAT PERBUATAN MELAWAN HUKUM YANG DILAKUKAN OLEH DEVELOPER (STUDI PUTUSAN NO.485.PDT.G/2018/PN.JKT.SEL) - Handy handy; Endang Pandamdari (Jurnal Hukum Adigama, 2021)
In 2014, the developer (developer) of the 45 Antasari apartment project located in the Cilandak area, West Cilandak Regency marketed apartment units in the form of apartments on a Pre Project Selling basis.In the sale of an apartment, the developer can do marketing before the construction is completed or commonly called the Pre Project Selling system, buying and selling must be written in the form of a Sales and Purchase Agreement. To make sales through pre-project sales, the developer must meet administrative requirements, one of which is a building permit. Moreover, because of sales and the purchase must be stated in the form of a Sale and Purchase Agreement, one of the conditions for getting a Sale and the Purchase Agreement is to have a building permit. Under construction of apartment developers too must have a permit to build a flat that is granted from the local government. But in reality,There are still apartment construction projects that do not have building permits, for example 45 Antasari Apartments. A building construction permit is needed to ensure the legal certainty of a building. Therefore, developer responsibility is required if he neglects someone's duties. With analysis, the authors suggest developer responsibility can be further elaborated, which will be further analyzed using normative legal research by examining existing primary and secondary legal materials collected and processed for the formulation of research conclusions.